2014
DOI: 10.1590/1982-021620143013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação audiológica em lactentes com agenesia de corpo caloso

Abstract: Objetivo verificar a ocorrência de alterações auditivas em lactentes com alteração do corpo caloso, comparando-os a crianças sem tal malformação. Métodos estudo de coorte dividido em duas partes: retrospectivo de 2008 a 2011 e prospectivo de 2011 a 2012. O grupo estudo foi constituído por 12 lactentes com diagnóstico de agenesia de corpo caloso e o grupo controlepor12 lactentes, pareados por idade pós concepcional e sexo. Todos realizaram Emissões Otoacústicas Evocadas por Estimulo Transiente, Potencial Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Studies have shown that dichotic listening skills and right ear advantage are affected by corpus callosum agenesis [5,9]. However, our study found no statistical differences between the ears to the absolute latencies and interpeak in ABR.…”
Section: Discussion Andcontrasting
confidence: 90%
See 1 more Smart Citation
“…Studies have shown that dichotic listening skills and right ear advantage are affected by corpus callosum agenesis [5,9]. However, our study found no statistical differences between the ears to the absolute latencies and interpeak in ABR.…”
Section: Discussion Andcontrasting
confidence: 90%
“…Studies show that corpus callosum agenesis is associated with right ear advantage and dichotic listening, and this reveals the dominance of the left hemisphere for speech [5].…”
Section: Introductionmentioning
confidence: 99%